Flow effect due to geometrical characteristics of pressure-swirl GDI atomizers - Mas Fawzi, Mohd Ali; Azhar, Abdul Aziz (The Institution of Engineers, Malaysia, 2011)
Link to publisher's homepage at http://www.myiem.org.my/